The Regulatory Mechanism of Extracellular Hsp90α on Matrix Metalloproteinase-2 Processing and Tumor Angiogenesis - Song, Xiaomin (American Society for Biochemistry and Molecular Biology, 2010)
Heat shock protein 90α (Hsp90α) is a ubiquitously expressed molecular chaperone that is essential for eukaryotic homeostasis. Hsp90α can also be secreted extracellularly, where it has been shown to be involved in tumor metastasis. Extracellular Hsp90α interacts with and promotes the proteolytic activity of matrix metalloproteinase-2 (MMP-2). However, the regulatory mechanism of Hsp90α on MMP-2 activity is still unknown. Here we show that Hsp90α stabilizes MMP-2 and protects it from degradation in tumor cells. Further investigation reveals that this stabilization effect is isoform-specific, ATP-independent, and mediated by the interaction between the Hsp90α middle domain and the MMP-2 C-terminal hemopexin domain. Moreover, this mechanism also applies to endothelial cells that secrete more Hsp90α in their proliferating status. Furthermore, endothelial cell transmigration, Matrigel plug, and tumor angiogenesis assays demonstrate that extracellular Hsp90α promotes angiogenesis in an MMP-2-dependent manner. In sum, this study provides new insights into the molecular mechanism of how Hsp90α regulates its extracellular client proteins and also reveals for the first time the function of extracellular Hsp90α in promoting tumor angiogenesis.